A Study on the Hysteresis Effect and Spectral Evolution in the Mini-Outbursts of Black Hole X-Ray Binary XTE J1550-564 - Dong, Ai-Jun; Liu, Chang; Ge, Kang; Liu, Xiang; Zhi, Qi-Jun; You, Zi-Yi (Frontiers in Astronomy and Space Sciences, 2021)
The well-known black hole X-ray binary XTE J1550-564 has been performed one normal outburst and three mini-outbursts by Rossi X-ray Timing Explorer satellite after 2000. In this work, we firstly report the hysteresis effect of the four outbursts. We find that the Hardness-intensity diagram of the normal outbursts in 2000 presents a q-like track, while the the Hardness-intensity diagrams of the three mini-outbursts lie on the right of the q-like track along with a Low/Hard state. The results suggest that there is not apparent hysteresis effect in the three mini-outbursts and the energy spectra are harder than the normal outburst at a same photon count rate. A similar result is also received in the X-ray photon index evolution, where the $Γ-F_{\rm 2-10keV}$ correlation of mini-outburst is still negative and the spectra are harder than the normal outburst at a same X-ray flux. The X-ray spectral evolution can be well explained by the transition from a advection-dominated accretion flow (ADAF) to Shakura-Sunyaev disk (SSD), which support that the mini-outburst is a smaller discrete accretion event.